Emotional Intelligence and Work Engagement: Connected or not? Evidence from the IT&C sector in Romania - Covrig, Mihaela; Goia (Agoston), Simona Irina; Igret, Ramona Stefania (Transformations In Business & Economics, 2025)
Emotional intelligence has been widely accepted as a very important feature of employees, influencing the way of thinking, the behaviour, and the interaction with other people. Traditionally, IT&C professionals are considered to have fewer soft skills than other types of professionals, as their education and work environment require task orientation, autonomy, reduced direct communication, and technical skills (Tang and Yin, 2008). The present research aims at investigating the emotional intelligence and its relationship with the work engagement among 450 Romanian IT&C professionals using a questionnaire-based survey. Two valid and reliable scales, the Wong and Law Emotional Intelligence Scale and Work (Wong and Law, 2002) and the Well-being Survey (UWES) (Schaufeli et al., 2017), were used to assess the concepts. The results of the study show that, contrary to our assumptions, the level of emotional intelligence of respondents is quite high, and that a direct relationship between the two concepts does exist. Our research reveals significant differences in multiple factors linked to Emotional Intelligence and Work Engagement according to various control variables, such as gender, age, residence, and income level.